2013
DOI: 10.3892/ijo.2013.1817
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of autophagy in matrine-induced gastric cancer cell death

Abstract: Matrine has potent antitumor activity against a broad variety of cancer cells and our previous study showed that both autophagy and apoptosis were activated during matrine-induced gastric cancer cell death. The aim of the present study was to determine the significance of autophagy in antineoplastic effects of matrine and the molecular mechanism by which matrine induces autophagy in gastric cancer cells. Western blot analysis showed that exposure of gastric cancer cells to matrine resulted in the extent of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 74 publications
3
30
0
Order By: Relevance
“…This suggests that matrine-induced protective autophagy partially suppressed apoptosis of cells. The present results are in agreement with other studies, which demonstrate that inhibition of autophagy by 3-methyladenine and CQ significantly increases matrine-induced apoptosis (9,10).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This suggests that matrine-induced protective autophagy partially suppressed apoptosis of cells. The present results are in agreement with other studies, which demonstrate that inhibition of autophagy by 3-methyladenine and CQ significantly increases matrine-induced apoptosis (9,10).…”
Section: Discussionsupporting
confidence: 94%
“…It has been demonstrated that matrine exhibits a potent anti-tumor activity in various cancer cell lines, including breast cancer and leukemia (6)(7)(8). In addition, studies have revealed that matrine induces protective autophagy in hepatocellular and gastric cancer (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…It's illustrated by these results that the autophagy induced by cisplatin is protective autophagy, some of which antagonize the apoptosis of gastric cancer cell, and chloroquine has the function of promoting cisplatin to induce apoptosis by inhibiting autophagy viability. It's similar to the research result on gastric cancer cell treated by 3-MA and matrine which was studied by Li et al (2013). It's also found that the expression of Caspase-3 and P53 is up-regulated in combined group, while the expression of apoptosis inhibiting protein Bcl-2 is down-regulated.…”
Section: Discussionsupporting
confidence: 72%
“…Matrine has been shown to produce a wide range of pharmacological effects and has been used to treat a variety of diseases, including viral hepatitis, neuropathic pain and isoproterenol-induced heart disease (11)(12)(13). In addition, significant antitumor effects have been found in gastric cancer, rhabdomyosarcoma, acute myeloid leukemia and breast cancer (14,15), and studies have shown that matrine exhibits antioxidant effects in a number of diseases. PD is mainly caused by damage to dopamine neurons, and oxidative stress is one of its important pathogenetic factors.…”
Section: Introductionmentioning
confidence: 99%